Antimicrobial Resistance of Bacterial Agents of the Upper Respiratory Tract of School Children in Buea, Cameroon - Ndip, RN; Ntiege, EA; Ndip, LM; Akoachere, J-F TK; Akenji, T Nkuo (Journal of Health, Population and Nutrition, 2009)
The study was aimed at determining bacterial agents of the upper respiratory tract and the susceptibility patterns of isolates to antibiotics. In total, 200 throat swabs were obtained from students attending differÂent boarding schools within the Buea Municipality and screened to obtain the prevalence of respiratory pathogens and to understand the antibiotic susceptibility patterns of isolates using standard microbiologiÂcal procedure and the disc-diffusion test. Of the 200 samples screened, 112 (56%) had positive cultures with the dominant bacterial pathogens being Haemophilus influenzae (20%), followed by Streptococcus pneuÂmoniae (15%), Klebsiella pneumoniae (11%), and Staphylococcus aureus (10%). Although 56% of the isolates were recovered from females compared to 44% from males, the difference was not statistically significant (p>0.05). Sixty-seven percent of the pathogens were isolated from the age-group of 10-13 years, 19.6% from the age-group of 14-17 years, and 12.5% from the age-group of 18-21 years. Antibiotic susceptibility testing revealed that gentamicin (92%) and cefuroxime (88.4%) were the most effective antibiotics against the isolates. Generally, susceptibility ranged from 0% to 92% depending on the antibiotic and the species of microorganism. Penicillin had the highest (100%) resistance to all the isolates. The findings revealed that students living in boarding schools in the Buea Municipality were at risk of acquiring upper respiraÂtory tract infections from their peers since the upper respiratory tract of more than 50% of the students was colonized with respiratory pathogens. Although multidrug-resistant strains of organisms were identiÂfied, gentamicin and cefuroxime are recommended as the first-line antibiotics of choice against the pathoÂgens. There is, therefore, a need for surveillance of nasopharyngeal carriage of resistant strains of these organisms, especially H. influenzae in unhealthy school children since the vaccine is yet to be introduced in Cameroon. The findings have clinical and epidemiological significance. Key words: Antibiotic resistance; Antibiotics; Bacteria; Child; Drug resistance, Microbial; Influenza; MicroÂbial susceptibility tests; Pneumonia; Respiratory tract infections; Cameroon doi:10.3329/jhpn.v26i4.1881 J Health Popul Nutr 2008 Dec:26(4):397-404